Morphological changes of rat jejunum after whole body gamma-irradiation and their impact in biodosimetry - Driák, D; Osterreicher, J; Vávrová, J; Řeháková, Z; Vilasová, Z (Physiological research, 2008)
Gastrointestinal form is the second stage of the Acute Radiation Syndrome (ARS) with a threshold dose of 8 Gy. It represents an absolutely lethal clinical-pathological unit, enteritis necro-hemorrhagica (duodenitis, jejunitis, ileitis, respectively) with unknown causal therapy. The purpose of our study has been to evaluate the morphological changes in a model of radiation-induced enteritis in rats and estimate the significance of changes in biodosimetry. Wistar rats were randomly divided into 21 groups, 10 animals per group. Samples of the jejunum were taken 24, 48, 72, and 96 h after the whole-body gamma-irradiation with the doses of 1, 5, 10, 15, and 20 Gy, and routinely stained with hematoxylin and eosin. Five morphometric markers--intercryptal distance, enterocytal height on the top and base of villus, length of basal lamina of 10 enterocytes and enterocytal width--in irradiated rat jejunum were examined. The results were compared with sham-irradiated control group. After lethal doses of irradiation, all morphometric parameters of jejunum significantly changed. With the exception of intercryptal distance, they might be considered as suitable biodosimetric markers under these experimental conditions. Our morphometry results in radiation-induced jejunitis are in accordance with those in other studies. We were the first who quantified morphological post-irradiation changes in animal jejunum. Some of them might be used under experimental conditions. This experimental study is a predecessor of the clinical assessment of a specific marker. Under clinical practice, the sensitive biodosimetric parameter could serve as one of the guidance for evaluation of the absorbed dose in irradiated troops as well as rescue workers. This is in accordance with tasks and Standardization Agreement of the North Atlantic Treaty Organization.
Keywords: enterocyty; krysa rodu Rattus; mužské pohlaví; Dose-Response Relationship, Radiation; jejunum; Male; Radiation Injuries, Experimental; Jejunal Diseases; Risk Assessment; Whole-Body Irradiation; Time Factors; enteritida; Rats; nemoci jejuna; záření gama; vztah dávky záření a odpovědi; radiometrie; potkani Wistar; Enteritis; bazální membrána; Animals; Jejunum; zvířata; Gamma Rays; experimentální radiační poranění; Basement Membrane; celotělové ozáření; Rats, Wistar; časové faktory; Radiometry; hodnocení rizik; Enterocytes